IMPLEMENTASI NILAI-NILAI PENDIDIKAN AKHLAK RASUL DALAM PENGAJIAN KITAB MAULID SHIMT AD-DURAR TERHADAP AKHLAK SANTRI DI PONDOK PESANTREN DARUR ROHMAN DEMAK - Muhamad Ulil Albab (Universitas Islam Sultan Agung, 2020)
This research aims to implement the values of moral education of the Apostle in the study of Mawlid SHIMT Ad-Durar to students in the boarding school in Darur Rohman Demak. Implementation of the value of moral education of the Apostle in the book Shimt al-Durar mawlid on the students in the boarding school Darur Rohman, has been performed well in the boarding school environment especially on the daily activities of students in the area of the cottage that is in place of morality. According to the display in the book of Shimt al-Durar mawlid when it will do anything especially when willing to learn him, he has always had the holy first, read the prayer and that is very important using morality. His habit was implemented at the boarding school Darur Rohman. The values of moral education in it are teaching the students to become people who have the moral sense of the prophet is with a sense of love and glorify him, say Sholawat and greetings to him. And teach the students to be people who have a sense of self-esteem that is by maintaining the purity of birth and inner and refraining from something that is not liked by Allah SWT, has a sense of shame, weak and gentle tempers, have a strong determination, far-off, is generous, authoritative.Keywords: Concept of value, Educational Morality of the Apostle, Book of Maulid SHIMT Ad-Durar